â€œKELUARGA YANG RAPUHâ€ MENDIDIK MORAL ANAK DI DALAM BUDAYA POSTMODERNISME - Moa, Antonius (LOGOS, 2015)
Nowdays, family as the union of persons are in fragile condition and in crisis. These things are happening as the effect of a strong cultural changing: from modernity to a fragile culture called postmodernity. What to do? How families handle this crisis? As the main actor in the mission and responsibility for children's moral educations, families are facing great challenges. To be able to do this mission and face this problem, families have to renew themselves continuously, find and create a model for their moral education for their children which comes from realities faced in particular time. It means, the families must know their reality because each family has different reality. AnotherÂ  invitation is to find way to integrate the values from modern and post-modern culture. Whith this solution hopefuly the crisis in the families will be lessen or solve in proper way.Â